Effectiveness and efficiency in the usage of software e-MySL© in learning Malaysian Sign Language (MySL) / Haziah Sa'ari ... [et al.] - Sa'ari, Haziah; Idrus, Marlia; Daud, Mohd Shamsul; Mansor, Kamarul Ariffin (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2009)
The Special Education particularly for the deaf has not seen much development over the decade as these students have not shown any significant improvement in examinations. This may be due to the fact that most teachers fail to master the Malaysian Sign Language (MySL) well. Up to this date, there is no adequate and accurate approach to address this issue. The software called e-MySL© is being developed to fill the needs of learning MySL using electronic gadgets. It is equipped with state-of the-art interactive module with interesting sound effects and colours and used the real model (or interpreter) with the clear face expressions and gesture. The objective of the research is to study the effectiveness and to measure the efficiency of the software. Data was obtained through questionnaires distributed to 135 respondents whom attending a full time Diploma in Sign Language Interpreter included the interpreters who are presently serving under the Malaysian Sign Language Training Centre (MySLTC) and Malaysian Federation of Deaf (MFD). Data was analyzed by descriptive statistic method. The results showed that 96% respondents agreed that e-MySL© is effective in recording the sign language. 88.9% respondents agreed that the audio/visual applications provided in the system are effective and self explanatory. The survey also indicated that 60.7% of the total respondents only took less than half hour to fully understand the interface and about 83.7% only took less than an hour. 71.9% of the respondents took less than an hour to fully understand a lesson thought through e-MySL© videos and 82.3% of respondents took less than an hour to do an exercise set in the lesson using the software. 98.5% of the total respondents agree that the exercises included in e-MySL© can really help them improved their sign language skills. The results showed that these factors: effectiveness, efficiency, flexibility and navigation facilities in e-MySL© have proactively contributed to the process of learning Malaysian Sign Language (MySL).